Predicting climate warming effects on green turtle hatchling viability and dispersal performance. (2nd January 2015) - Cavallo, Catherine; Dempster, Tim; Kearney, Michael R.; Kelly, Ella; Booth, David; Hadden, Kate M.; Jessop, Tim S.
Summary: Ectotherms are taxa considered highly sensitive to rapid climate warming. This is because body temperature profoundly governs their performance, fitness and life history. Yet, while several modelling approaches currently predict thermal effects on some aspects of life history and demography, they do not consider how temperature simultaneously affects developmental success and offspring phenotypic performance, two additional key attributes that are needed to comprehensively understand species responses to climate warming. Here, we developed a stepwise, individual‐level modelling approach linking biophysical and developmental models with empirically derived performance functions to predict the effects of temperature‐induced changes to offspring viability, phenotype and performance, using green sea turtle hatchlings as an ectotherm model. Climate warming is expected to particularly threaten sea turtles, as their life‐history traits may preclude them from rapid adaptation. Under conservative and extreme warming, our model predicted large effects on performance attributes key to dispersal, as well as a reduction in offspring viability. Forecast sand temperatures produced smaller, weaker hatchlings, which were up to 40% slower than at present, albeit with increased energy stores. Conversely, increases in sea surface temperatures aided swimming performance. Our exploratory study points to the need for further development of integrative individual‐based modelling frameworks to better understand the complex outcomes of climate change for ectotherm species. Such advances could better serve ecologists to highlight the most vulnerable species and populations, encouraging prioritization of conservation effort to the most threatened systems. Abstract : Lay Summary